Assessing the variability and the role of inflammatory cytokines and monocyte chemoattractant protein-1 (MCP-1) in predicting stroke among hypertensives: A case-control study - Samuel Asamoah Sakyi; Afia Serwaa Opoku; Benjamin Amoani; Bright Oppong Afranie; Alexander Kwarteng; Richard Dadzie Ephriam; Stephen Opoku; Ebenezer Senu; Ebenezer Aidoo; Fred Stephen Sarfo (Dialogues in Health, 2022)
Background: Atherosclerosis is a complex lipid-driven inflammatory disease in which numerous cell types and inflammatory mediators are involved in the progression of hypertension to stroke. Mediators’ markers that could predict the progression of hypertension to stroke are of research importance. We assessed the predictive value of individual and combined cytokines and monocyte chemoattractant protein-1 (MCP-1) among hypertensives with or without stroke. Methods: In a case-control study, we enrolled 63 cases with stroke and hypertension (HPT-S), 59 stroke-free hypertensives (HPT), and 53 stroke free normotensives as controls (CS). Sociodemographic data and blood samples were collected for the estimation of Interleukin-10 (IL-10), IL-6, IL-8, IL-1β and monocyte chemoattractant protein-1 (MCP-1) using commercially available ELISA kits from Biobase Biotech, Shanghai, China. The Receiver Operator Characteristics (ROC) analysis was used to calculate diagnostic accuracy for cytokines in predicting stroke among hypertensives. A combined bioscore model of IL-10 and MCP-1 was generated to predict stroke among hypertensives. The multiple logistic regression analysis was used to assess the chances of IL-10 and MCP-1 in predicting stroke among hypertensives. Statistical analyses were performed using R-language. Results: The HPT-S group had significantly higher levels of MCP-1 and IL-10 compared to the HPT and CS groups (p < 0.05). There was no significant difference in IL-1β, IL-8 and IL-6 amongst the three study groups. MCP-1 and IL-10 were predictive of stroke occurrence among hypertensives and were used to develop a bioscore model. An elevated MCP-1 and IL-10 with a bioscore 2 had a predictive accuracy of 0.81, a sensitivity of 0.77 and specificity of 0.84. At a bioscore of 1, the sensitivity and specificity for predicting stroke among hypertensives was 97.0% and 61.0% respectively. In a binary logistic regression, having a bioscore of 1 [aOR = 20.43, 95% CI (2.17–192.62), p = 0.008] or 2 [aOR = 26.00, 95% CI (2.92–231.31), p = 0.003] were significantly associated with stroke occurrence among hypertensives. Conclusion: Higher levels of IL-10 with a concomitant level of MCP-1 could serve as a good predictor of stroke among hypertensives. Subsequently, MCP-1 may prove useful as a therapeutic target for atherosclerosis in hypertensives. Combined bioscore of MCP-1 and IL-10 could serve as a good predictor of stroke among hypertensives.